Conformal Carbon Nitride Coating as an Efficient Hole Extraction Layer for ZnO Nanowires‐Based Photoelectrochemical Cells. Issue 24 (31st October 2017) - Hajduk, Špela; Berglund, Sean P.; Podlogar, Matejka; Dražić, Goran; Abdi, Fatwa F.; Orel, Zorica C.; Shalom, Menny
Abstract: Charge transfer at the semiconductor–electrolyte junction is one of the main challenges for further improvement of photoelectrochemical (PEC) water splitting cells due to the poor surface catalytic properties of most semiconductors for the water oxidation reaction. Here it is shown, for the first time, that a conformal and thin carbon nitride (CN) layer can efficiently extract holes from ZnO nanowires (NWs), leading to a great enhancement of both PEC performance and stability in alkaline solution. The conformal CN coating is acquired by using a new synthetic method which involves the deposition of small supramolecular assemblies on ZnO‐NWs as a seeding layer for the CN growth. Detailed PEC characterization reveals that the CN facilitates the hole transfer from the ZnO‐NWs to the electrolyte and acts as a protective shell, resulting in 3.5 times higher current densities and high external quantum efficiencies at 1.23 V versus RHE compared to the pristine ZnO‐NWs. Abstract : Conformal carbon‐nitride (CN) layer acts as an efficient hole extraction layer for ZnO nanowires (NWs)‐based photoelectrochemical cells. The homogenous coating is acquired by the introduction of a new synthetic approach involving the deposition of small supramolecular‐assembly seeds on ZnO‐NWs prior the CN growth. The best device exhibits impressive current densities and external quantum efficiencies at 1.23 V versus reversible hydrogen electrode (RHE).